Species Composition and Conservation Status of Ornamental Fishes in Khambrenga Wetland, Kamrup District, Assam, India - Rahman , Aminur; Kalita , Abinash; Islam , Sajidul; Deka , Parag (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2024)
Ornamental fish culture, also known as aquariculture, is a significant industry globally, contributing to foreign exchange earnings and employment generation. India, particularly the northeastern region, is endowed with diverse indigenous ornamental fish species. However, the ornamental fish trade in India remains relatively underdeveloped. This study aimed to document the ornamental fish diversity in Khambrenga Beel, a freshwater wetland located near Guwahati City, Assam, India. From December 2022 to April 2023, fish samples were collected and photographed in the study area. Local knowledge and identification literature were utilized to identify the fish species, while the IUCN Red List was referenced to determine their conservation status. A total of 48 species belonging to 30 genera, 20 families, and 10 orders of ornamental fishes were recorded in Khambrenga Beel. The Cypriniformes and Perciformes orders were the most diverse, comprising 16 species each. The majority of the recorded species were categorized as least concern (LRlc), indicating a relatively stable conservation status. However, three species were categorized as near threatened (NT), one species as vulnerable (VU), and one species as endangered (EN). The abundance of ornamental fishes varied across different sampling sites and seasons, reflecting the influence of habitat heterogeneity and seasonal dynamics. The findings highlight the importance of conserving Khambrenga Beel's unique ecosystem and its diverse ornamental fish species. Conservation measures such as habitat protection and sustainable fishing practices are crucial for ensuring the long-term survival of these species. This study provides valuable information for the development of conservation strategies to protect the ornamental fish populations in Khambrenga Beel, thereby contributing to the overall conservation of indigenous ornamental fishes in India.